MeCoCo: A Context-Aware System for Mediated Communications - George, Sebastien; Lekira, Aina Sylviane (International Journal of Interactive Mobile Technologies (iJIM), 2009)
In this paper, we explore the potential of contextual communications with mobile technologies. Context-aware applications allow information or services delivery relevant to users at a given time. One of the two objectives of our work is to propose a generic usersâ?? context model for mediated communications. This model is based on six dimensions: Userâ??s profile, Activity, Device, Environment, Location and Time. In addition, to illustrate the utility and to validate the proposed approach, we design a prototype named MeCoCo (Mediated Contextual Communications) with a particular interface favoring the search of interesting contacts and messages. The MeCoCo prototype can highlight a dimension of contextual information compared to the others.